Altenbergove in Cankarjeve podobe krhkih žensk - Čeh Steger, Jožica (Slavia Centralis, 2024)
In the Vienna of the fin-de-siecle, Peter Altenberg and Ivan Cankar articulated different variants of the femme fatale and the femme enfant, which were an expression of the literary aestheticism and tabuing of feminism at the end of the 19th century. This paper presents images of fragile women in Altenberg’s collection Wie ich es sehe (1896) and in Cankar’s Vinjete (1899). Cankar frequently shaped the femme fragile in accordance with the decadent aesthetics of sickliness and death, while within the construct of woman-child and her angelic image he also articulated her unbridled erotic nature. Altenberg merged the descriptions of angelically beautiful sexless fragile women and ideal girls of prepubertal age with a programme of healthy life in nature, however, they cannot avoid the male erotic gaze and the transfiguration of his erotic fantasies.
Keywords: Altenberg, Peter; Cankar, Ivan; eroticism; erotika; kratka proza; short prose